Exploiting cell metabolism for biocatalytic whole-cell transamination by recombinant Saccharomyces cerevisiae - Weber, Nora (Appl Microbiol Biotechnol, 2014)
The potential of Saccharomyces cerevisiae for biocatalytic whole-cell transamination was investigated using the kinetic resolution of racemic 1-phenylethylamine (1-PEA) to (R)-1-PEA as a model reaction. As native yeast do not possess any ω-transaminase activity for the reaction, a recombinant yeast biocatalyst was constructed by overexpressing the gene coding for vanillin aminotransferase from Capsicum chinense. The yeast-based biocatalyst could use glucose as the sole co-substrate for the supply of amine acceptor via cell metabolism. In addition, the biocatalyst was functional without addition of the co-factor pyridoxal-5′-phosphate (PLP), which can be explained by a high inherent cellular capacity to sustain PLP-dependent reactions in living cells. In contrast, external PLP supplementation was required when cell viability was low, as it was the case when using pyruvate as a co-substrate. Overall, the results indicate a potential for engineered S. cerevisiae as a biocatalyst for whole-cell transamination and with glucose as the only co-substrate for the supply of amine acceptor and PLP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-014-5576-z) contains supplementary material, which is available to authorized users.